Over-Expression of the Mycobacterial Trehalose-Phosphate Phosphatase OtsB2 Results in a Defect in Macrophage Phagocytosis Associated with Increased Mycobacterial-Macrophage Adhesion - Li, Hao; Wu, Mei; Shi, Yan; Javid, Babak (Frontiers in Microbiology, 2016)
Trehalose-6-phosphate phosphatase (OtsB2) is involved in the OtsAB trehalose synthesis pathway to produce free trehalose and is strictly essential for mycobacterial growth. We wished to determine the effects of OtsB2 expression on mycobacterial phenotypes such as growth, phagocytosis and survival in macrophages. Mycobacterium bovis-BCG (BCG) over-expressing OtsB2 were able to better survive in stationary phase. Over-expression of OtsB2 led to a decrease in phagocytosis but not survival in THP-1 macrophage-like cells, and this was not due to a decrease in general macrophage phagocytic activity. Surprisingly, when we investigated macrophage-mycobacterial interactions by flow cytometry and atomic force microscopy, we discovered that BCG over-expressing OtsB2 have stronger binding to THP-1 cells than wild-type BCG. These results suggest that altering OtsB2 expression has implications for mycobacterial host-pathogen interactions. Macrophage-mycobacteria phagocytic interactions are complex and merit further study.